(untitled) (Fiep Bulletin - online, 2014)
Leisure time behaviour patterns of young women and the place of engagement in physical activities (PA) in it, as well as preferences for them were the aims. The data were collected with anonymous poll among 151 first-year female students and processed by frequency analysis and percentage computation. The findings indicate the young women from Pula mostly do sedentary activities (learning, reading, TV watching, internet browsing). Slightly less than a half of the subjects (73; 48.04%) were engaged in any kind of physical activity, but irregularly and in the amount insufficient to produce any positive effect on their health. These activities include: (running, walking, cycling, roller-blading, aerobics, pilates, fitness, and folklore dancing. Although the students reported to have a relatively large amount of daily leisure time, the main reason for not engaging in exercise was lack of time. However, even the inactive students had certain preferences of would-be PA: they would be regularly engaged in: team sport games (team handball and volleyball), and in running, cycling, swimming, roller-blading, and aerobics. Occasionaly, they would do: volleyball, basketball, skiing, swimming, team handball, pilates, table tennis, hiking, running and cycling. The study reinforced the need for organized intervention to alter physical-activity-related behavior of young women.